If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -4) = 6y + -11 + -1y Reorder the terms: 2(-4 + y) = 6y + -11 + -1y (-4 * 2 + y * 2) = 6y + -11 + -1y (-8 + 2y) = 6y + -11 + -1y Reorder the terms: -8 + 2y = -11 + 6y + -1y Combine like terms: 6y + -1y = 5y -8 + 2y = -11 + 5y Solving -8 + 2y = -11 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -8 + 2y + -5y = -11 + 5y + -5y Combine like terms: 2y + -5y = -3y -8 + -3y = -11 + 5y + -5y Combine like terms: 5y + -5y = 0 -8 + -3y = -11 + 0 -8 + -3y = -11 Add '8' to each side of the equation. -8 + 8 + -3y = -11 + 8 Combine like terms: -8 + 8 = 0 0 + -3y = -11 + 8 -3y = -11 + 8 Combine like terms: -11 + 8 = -3 -3y = -3 Divide each side by '-3'. y = 1 Simplifying y = 1
| 8x+9+6x-3+90=180 | | -16.128=2.1r+1.7r | | 8n^2=64n(logn) | | 4(m-6)-5(m+2)= | | (60x+62y)-(-26x+2y)= | | 2x^2-3x+2=x^2 | | 4(10x-7)+12(3x+14)=76216 | | 60=10x+6-7+1 | | 2x+2(2x-4)=64 | | 16-1+21=x-1 | | 9+.19=22+.14x | | 2b+9=1811 | | 3p+6p-6p+1=4 | | 5r^2+6=17r | | -3(4+1)+6x=4(2x-6) | | 9k^2+19k+12=10 | | 3n+2=2n+5 | | 9+.19x=22+14x | | -[3x-(2x+5)]-7=-4[3(2x-4)-3x] | | 8(7-5x)=-40-8x | | 4x^2+y^2=61 | | 55+.70x=.80x | | 1w=-7 | | 6+n=1+2n | | 24.6+34=9.54 | | -5-15n=-46 | | 3v^2-13v=-4 | | 2(6+24)=30 | | -(7r-2)=-23-2r | | 7y^2+3+3y^2-8= | | 3x=34 | | 90992+8.75=15535+24x |